Effects of parental beliefs regarding the control of children’s behaviour on discipline principles - Κόκκινος Κωνσταντίνος; Παναγιώτου Γεωργία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF